2015
DOI: 10.1093/heapol/czv042
|View full text |Cite
|
Sign up to set email alerts
|

Valuing the work of unpaid community health workers and exploring the incentives to volunteering in rural Africa

Abstract: Community health worker (CHW) programmes are currently being scaled-up in sub-Saharan Africa to improve access to healthcare. CHWs are often volunteers; from an economic perspective, this raises considerations whether reliance on an unpaid workforce is sustainable and how to appropriately cost and value the work of CHWs. Both these questions can be informed by an understanding of CHWs’ workload, their opportunity costs of time and the perceived benefits of being a CHW. However, to date few studies have fully e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 52 publications
4
77
1
Order By: Relevance
“…The daily volume of time spent on childcare was modest both before and after the intervention, and the bulk of the time was spent on diagnosis of malaria, with a smaller fraction on treatment. Our findings are considerably less than the 4.8 hours per day found in Ghana, but comparable to findings in Uganda reporting about 40 minutes daily taken by CHWs to provide integrated care for common childhood illnesses [10, 11]. …”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The daily volume of time spent on childcare was modest both before and after the intervention, and the bulk of the time was spent on diagnosis of malaria, with a smaller fraction on treatment. Our findings are considerably less than the 4.8 hours per day found in Ghana, but comparable to findings in Uganda reporting about 40 minutes daily taken by CHWs to provide integrated care for common childhood illnesses [10, 11]. …”
Section: Discussionsupporting
confidence: 66%
“…In Burkina Faso, the hourly minimum wage was 176.83 XOF (about 28 292 XOF per month or USD $52.10) [14]. In Nigeria, the monthly minimum wage was 18 000 Nigerian naira (NGN) (USD $100) [14] and in Uganda, USD $54 [11]. CHWs’ time value is presented in US dollars (USD $) using average exchange rates between 2014 and 2015: USD $1 = 542.75 XOF (Burkina Faso) and USD $1 = 180 NGN ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The driving force for their active involvement needs to be investigated in terms of motivation. It was observed in Uganda, for example, that volunteer community health workers (CHWs) were actually participating with an expectation of future rewards (Kasteng et al, 2016). In contrast, a qualitative study from this region of Ethiopia suggested the current dominance of intrinsic motivators (such as community recognition and appreciation) among the HEWs and their supporters (Tulloch et al, 2015).…”
Section: Number Of Householdsmentioning
confidence: 99%
“…At the same time, monetary incentives and means of transport such as bicycles were found to be essential for VHTs to undertake their roles. Other studies also indicate a nuanced approach to CHW motivation requiring both financial and non-financial incentives [30][31][32].…”
Section: Strengthening Chwsmentioning
confidence: 99%